Peran Moderasi Ukuran Perusahaan pada Pengaruh Struktur Modal dan Profitabilitas terhadap Nilai Perusahaan - Victor, Victor; Indah, Nopiani (Universitas Sains dan Teknologi Komputer, 2025)
The size of the company as a moderator in defining the correlation between capital structure, profit, and firm value is the focus of this study. Adopting a quantitative associative approach, this research focuses on the non-cyclical consumer sector registered on the Indonesia Stock Exchange (IDX) for the period 2020–2023. Of the 125 companies, 73 were purposively selected to create the research sample, yielding 292 observations after excluding entities with incomplete data and those with special monitoring status. The authors gathered secondary data from audited yearly financial reports through the IDX portal and corporate websites. The analysis used quasi-moderation techniques by combining independent variables, moderation, and interaction in a single regression model, processed through EViews 13. The research results show that capital structure has a significant positive impact on firm value, while profitability has no significant impact. Firm size has been shown to affect the relationship that exists between capital structure and firm value, but it does not moderate the association between profitability and firm value. These findings confirm that leverage’s effectiveness in increasing firm value is independent of company size and that profitability is not a primary determinant in this context. This research provides empirical evidence to advance capital structure theory and to inform executives’ strategic financial decisions and investors’ evaluations of corporate outlooks.